2015
DOI: 10.1002/ijc.29500
|View full text |Cite
|
Sign up to set email alerts
|

Association ofPSCArs2294008 gene variants with poor prognosis and increased susceptibility to gastric cancer and decreased risk of duodenal ulcer disease

Abstract: Two recent genome-wide association studies in Asians have reported the association between the PSCA (prostate stem cell antigen) rs2294008C>T gene polymorphism and two Helicobacter pylori infection-related diseases such as gastric cancer (GC) and duodenal ulcer (DU). Since rs2294008 allele frequencies differ notably among ethnicities, we aimed to assess the role of rs2294008 on the susceptibility to GC and DU in a Caucasian population in Spain. Moreover, the relevance of rs2294008 on GC prognosis was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 43 publications
3
26
0
5
Order By: Relevance
“…The studied cancer type included gastric cancer [8, 14-17, 20-22, 25, 26, 31, 32, 34, 39, 41-43], bladder cancer [9, 18, 23, 28, 35, 40], prostate cancer [19], esophageal cancer [20, 33], breast cancer [24], colorectal cancer [27], and gallbladder cancer [29, 30]. In term of ethnicity, 21 studies were performed among Asians, 10 studies among Caucasians, and one study among Africans.…”
Section: Resultsmentioning
confidence: 99%
“…The studied cancer type included gastric cancer [8, 14-17, 20-22, 25, 26, 31, 32, 34, 39, 41-43], bladder cancer [9, 18, 23, 28, 35, 40], prostate cancer [19], esophageal cancer [20, 33], breast cancer [24], colorectal cancer [27], and gallbladder cancer [29, 30]. In term of ethnicity, 21 studies were performed among Asians, 10 studies among Caucasians, and one study among Africans.…”
Section: Resultsmentioning
confidence: 99%
“…Some genetic variants are associated with patients' prognosis of GC. García-González et al [39] identified the rs2294008T variant as a prognosis factor associated with worse overall survival in patients with diffuse-type GC (hazard ratio = 1.85; 95% confidence interval = 1.12-3.06). PSCA rs2294008 polymorphism is involved in the prognosis of the diffuse type of GC in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer GWAS facilitated the identification of two tumor subtypes -gastric cardia and gastric noncardia -in a population study [101]. In another independent study, PSCA rs2294008 was found to be associated with increased risk of gastric cancer and decreased risk of duodenal cancer [58].…”
Section: • Gastric Cancermentioning
confidence: 99%
“…Genome-wide methylation [52]; the major genes affected were PTK2, RND1, and UBL3 which regulate recurrence of cancer [52] Sensitive locus for mutations 4q21 [22] 4q21 [22] SNP rs1229984 in ADH1B [22] SNP rs7922612 related with survival [22] Germline copy number loss of UGT28 and gain of PLEC [53] Gastric cancer FAT4, a novel tumor suppressor identified by exome sequencing gets inactivated due to hypermethylation (field canerization) [54] Epigenetic silencing of GLDC [57] Susceptibility locus 8q24 [55] 8q24.3 [58] SNP rs4733616 [55] SNP rs2294008 was associated with decreased risk of duodenal cancer [55] SNP rs2294008 was found to be associated with increased risk of gastric cancer and decreased risk of duodenal cancer [58] SNP rs2976392 [22] Loss of CNV at 5q22 region surrounding APC [56] Hepatocellular carcinoma (liver cancer)…”
Section: Cervical Cancermentioning
confidence: 99%